A comprehensive investigation of the accuracy and reproducibility of a multitarget single isocenter VMAT radiosurgery technique. Issue 12 (26th November 2013) - Thomas, Andrew; Niebanck, Michael; Juang, Titania; Wang, Zhiheng; Oldham, Mark
Abstract : Purpose: : Recent trends in stereotactic radiosurgery use multifocal volumetric modulated arc therapy (VMAT) plans to simultaneously treat several distinct targets. Conventional verification often involves low resolution measurements in a single plane, a cylinder, or intersecting planes of diodes or ion chambers. This work presents an investigation into the consistency and reproducibility of this new treatment technique using a comprehensive commissioned high‐resolution 3D dosimetry system (PRESAGE ® /Optical‐CT). Methods: : A complex VMAT plan consisting of a single isocenter but five separate targets was created in Eclipse for a head phantom containing a cylindrical PRESAGE ® dosimetry insert of 11 cm diameter and height. The plan contained five VMAT arcs delivering target doses from 12 to 20 Gy. The treatment was delivered to four dosimeters positioned in the head phantom and repeated four times, yielding four separate 3D dosimetry verifications. Each delivery was completely independent and was given after image guided radiation therapy (IGRT) positioning using Brainlab ExacTrac and cone beam computed tomography. A final delivery was given to a modified insert containing a pin‐point ion chamber enabling calibration of PRESAGE ® 3D data to dose. Dosimetric data were read out in an optical‐CT scanner. Consistency and reproducibility of the treatment technique (including IGRT setup) was investigated by comparing the dose distributions in the four inserts, and with the predicted treatment planning system distribution. Results: : Dose distributions from the four dosimeters were registered and analyzed to determine the mean and standard deviation at all points throughout the dosimeters. A dose standard deviation of <3% was found from dosimeter to dosimeter. Global 3D gamma maps show that the predicted and measured dose matched well [3D gamma passing rate was 98.0% (3%, 2 mm)]. Conclusions: : The deliveries of the irradiation were found to be consistent and matched the treatment plan, demonstrating high accuracy and reproducibility of both the treatment machine and the IGRT procedure. The complexity of the treatment (multiple arcs) and dosimetry (multiple strong gradients) pose a substantial challenge for comprehensive verification. 3D dosimetry can be uniquely effective in this scenario.